2017
DOI: 10.1038/s41598-017-01562-1
|View full text |Cite
|
Sign up to set email alerts
|

Participants with Normal Weight or with Obesity Show Different Relationships of 6-n-Propylthiouracil (PROP) Taster Status with BMI and Plasma Endocannabinoids

Abstract: Reduced taste sensitivity to 6-n-propylthiouracil (PROP), a genetic trait regarded as a general index for oral chemosensory perception, has been associated with a calorie-rich food preference and lower circulating endocannabinoid levels in participants with normal weight (NW), which suggests an adaptive mechanism to maintain a lean phenotype. In this study, we assessed whether participants with obesity (OB) show different patterns of plasma endocannabinoids and lipid metabolism biomarkers from those of NW, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 73 publications
6
30
0
Order By: Relevance
“…Our results confirm our previous reports (Tomassini Barbarossa et al, 2013 ; Carta et al, 2017 ) that genetic factors influencing dietary preferences affect fatty acid metabolism and circulating levels of endocannabinoids, differently in NW and OB subjects. Interestingly, in NW with the AA genotype of the rs1761667 polymorphism in CD36 , characterized by a lower expression of CD36 protein with respect to subjects carrying the G allele, as previously shown (Ghosh et al, 2011 ; Love-Gregory et al, 2011 ), we found a marked reduction of RBC SAFA levels and PA/LA and PA/ARA ratios which have been used as markers of DNL (Jacobs et al, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results confirm our previous reports (Tomassini Barbarossa et al, 2013 ; Carta et al, 2017 ) that genetic factors influencing dietary preferences affect fatty acid metabolism and circulating levels of endocannabinoids, differently in NW and OB subjects. Interestingly, in NW with the AA genotype of the rs1761667 polymorphism in CD36 , characterized by a lower expression of CD36 protein with respect to subjects carrying the G allele, as previously shown (Ghosh et al, 2011 ; Love-Gregory et al, 2011 ), we found a marked reduction of RBC SAFA levels and PA/LA and PA/ARA ratios which have been used as markers of DNL (Jacobs et al, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, we have found that taste sensitivity for the bitter taste of 6-n-propylthiouracil (PROP), regarded as a general oral marker for chemosensory perception, food preference and BMI (Tepper, 2008 ; Padiglia et al, 2010 ; Tepper et al, 2011 , 2014 ; Melis and Tomassini Barbarossa, 2017 ; Melis et al, 2017 ), affects lipid metabolism in normal weight (NW) (Tomassini Barbarossa et al, 2013 ) and obese (OB) (Carta et al, 2017 ) subjects. Peculiarly, in subjects with obesity, we showed an increased BMI and decreased levels of plasmatic endocannabinoids in subjects with extremely elevated PROP sensitivity, also named super-testers, vs. subjects with reduced PROP sensitivity (non-tasters).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, overproduction of PA by DNL, activated by physiopathological conditions and chronic nutritional imbalance, leads to a systemic inflammatory response and a metabolic dysregulation, resulting in dyslipidemia, insulin resistance and a dysregulated fat deposition and distribution (Donnelly et al, 2005 ). Remarkably, a recent study has shown that taste sensitivity to 6-n-propylthiouracil (PROP), a genetic trait of oral chemosensory perception, can influence DNL, and therefore PA red blood cell levels, in association to changes in circulating endocannabinoid levels (Carta et al, 2017 ). Noteworthy, it has been shown that treatment with endocannabinoid receptor agonist increased DNL in the mouse liver or in isolated hepatocytes (Osei-Hyiaman et al, 2005 ).…”
Section: Endogenous Pa Biosynthesis By Dnl and Metabolic Outcomesmentioning
confidence: 99%
“…Another study suggests that reduced taste sensitivity to PROP has been associated with preferences for foods with more calories and lower circulating endocannabinoid levels in subjects with normal BMI (p = 0.00012) and higher BMI and lower circulating endocannabinoids in subjects with obesity and that were supertasters than in obese non-tasters (p = 0.023, p = 0.003). Those results might suggest that lower concentration of circulating endocannabinoids should be an adaptative mechanism to counteract excess of fat accumulation and PROP taste sensitivity is associated with food preferences and may determine long-term metabolic changes and body composition [31]. Also, Tomassini et al [32] showed that taste sensitivity to PROP is associated with endocannabinoid (2-arachidonoylglycerol (2-AG), anandamide (AEA)) plasma levels in normal-weight individuals.…”
Section: Bitterness Perception and Other Diseasesmentioning
confidence: 99%